Advanced Therapeutic Dressings for Effective Wound Healing--A Review - Boateng, Joshua; Catanzano, Ovidio (Journal of pharmaceutical sciences, 2015)
Advanced therapeutic dressings that take active part in wound healing to achieve rapid and complete healing of chronic wounds is of current research interest. There is a desire for novel strategies to achieve expeditious wound healing because of the enormous financial burden worldwide. This paper reviews the current state of wound healing and wound management products, with emphasis on the demand for more advanced forms of wound therapy and some of the current challenges and driving forces behind this demand. The paper reviews information mainly from peer-reviewed literature and other publicly available sources such as the US FDA. A major focus is the treatment of chronic wounds including amputations, diabetic and leg ulcers, pressure sores, and surgical and traumatic wounds (e.g., accidents and burns) where patient immunity is low and the risk of infections and complications are high. The main dressings include medicated moist dressings, tissue-engineered substitutes, biomaterials-based biological dressings, biological and naturally derived dressings, medicated sutures, and various combinations of the above classes. Finally, the review briefly discusses possible prospects of advanced wound healing including some of the emerging physical approaches such as hyperbaric oxygen, negative pressure wound therapy and laser wound healing, in routine clinical care.